Impact of gender on self-assessment accuracy among fourth-year French medical students on faculty’s online Objective Structured Clinical Examinations - Sylvain Bodard; Donia Bouzid; Valentine Marie Ferré; Claire Carette; Joelle Kivits; Yann Nguyen; Michael Thy; Ugo Marchèse; Bénédicte Oulès; Lina Khider; Christian de Tymowski; Nelly Burnichon; et al. (BMC Medical Education)
Abstract Background Historically, women have been shown to underestimate their abilities, while men often assess themselves more accurately or overestimate. This study aims to determine self-assessment accuracy during online Objective Structured Clinical Examinations (OSCEs) according to gender. Methods A prospective study was conducted among fourth-year medical students at Paris Cité University during faculty training OSCEs, utilizing Zoom® software for remote participation. Students and evaluators assessed performances using 5-point Likert scales for medical knowledge, interpersonal skills, and overall performance. Additionally, students predicted their grade out of twenty. The assessment covered three independent stations. Results This study included 259 medical students (177 women, 81 men, one non-binary (excluded from further analyses)) evaluated by 130 physicians. Evaluator scores did not differ according to students’ gender (total score out of 20: men: 10.25 ± 3.45, women: 10.23 ± 3.44 p = 0.817) nor students’ self-assessments (total score out of 20: men: 11.22 ± 3.02, women: 11.00 ± 3.03; p = 0.466) whatever the domains and stations (all p > 0.05). The difference (delta) between self-assessment and evaluator scores for medical knowledge (men: 0.73 ± 1.00, women: 0.64 ± 1.02; p = 0.296), interpersonal skills (men: 1.02 ± 1.06, women: 0.93 ± 1.09; p = 0.296), and total score (men: 0.98 ± 3.41, women: 0.68 ± 3.42; p = 0.296) showed no gender differences. Further analysis categorized students based on their self-assessment accuracy, revealing that both men and women displayed a high ratio of accurate self-assessments (78.1% for overall performance across all stations), with minimal overestimation observed in both genders (20.9% for overall performance across all stations). Instances of overestimation or underestimation were rare and not consistent over the 3 stations, indicating that such misjudgments are likely situational rather than inherent traits. Discussion This study reveals similar self-assessment accuracy according to gender in online training OSCEs suggesting a shift towards gender-equitable self-perceptions among medical students compared to previous studies. Research remains necessary to corroborate these results and explore the underlying factors contributing to this shift in self-perception.